2011
DOI: 10.1007/978-3-642-21729-6_197
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Magnetic Fields Effects on Stem Cell Differentiation

Abstract: Abstract-The objective of this paper is to provide the fundamental mathematical formula to predict the effect of magnetic fields (MF) on stem cell differentiation. The data were reviewed from journals related to the effects of magnetic fields on stem cell differentiation. These data were given a value for differentiation which is related to their MF strength with these conditions; MF strength that does not affect the stem cell differentiation given the value of zero, MF strength that results in stem cells deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Nevertheless, some concerns regarding their use at a therapeutic level have been raised (D'Angelo et al, 2015). These predominantly pertain to the use of specific amplitudes, frequencies, and exposure times (Miskon and Uslama, 2011).…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%
“…Nevertheless, some concerns regarding their use at a therapeutic level have been raised (D'Angelo et al, 2015). These predominantly pertain to the use of specific amplitudes, frequencies, and exposure times (Miskon and Uslama, 2011).…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%
“…Because of the negative connotations revolving around EMF and the effects of radiation, concerns have been raised regarding its usage at the therapeutic level (D'Angelo et al, 2015). To determine whether EMF is either dangerous or harmless, certain parameters such as amplitude, frequency, and exposure time are needed to be considered (Carpenter and Ayrapetyan, 1994;Miskon and Uslama, 2011). Two studies have shown that EMF exposure within a specified range does not cause any cytotoxic effects in MSCs.…”
Section: Cytotoxic and Genotoxic Effects Of Emf On Mscsmentioning
confidence: 99%